(3Gdabg GdCcHQs - (3GdgGTej GdbQTj GdeWdHj GdTGaYj, CHh YHO Gddg, eMeO Hf EOQjS Hf GdYHGS, (B204 (3gs ((3YeQ Hf jhSa Hf YeQ Hf jhSas)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf bGd GdTGaYj gPG cJGH PcQfG ajg XhGgQ GdeSGFd aj CUhd GdOjf hSejfGg Gdabg GdCcHQ aUd bGd GdEeGe GYdehG GSYOce Gddg Cf cd ecdas
(3BNQgG (B:s
(3bGd ef SH CUMGHj abO SHfj hef SHfj abO SH Gddg JYGdi hef SH Gddg JYGdi aYdjg dYfI Gddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 26s
(3eYLe GdeDdajf (B3 / 116s
(3cTa GdXfhf (B2 / 1287s
(3TPQGJ GdPgH (B2 / 9s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs